Active Immunization Against NMDA NR1 Subunit as a Model of Autoimmune Encephalitis. (5th December 2022) - Jachimiec, Grace; Motlagh, Negin Jalali; Lin, Chih-Chung; Kuellenberg, Enrico; Planagumà, Jesús; Wojtkiewicz, Gregory; Chen, John; Linnoila, Jenny
Abstract : Objective: To identify and develop the optimal active immunization induction method for NMDAR encephalitis in rodents. Background: Encephalitis is a devastating neurologic disorder with high morbidity and mortality. Many cases are autoimmune. N-Methyl-D-aspartic acid receptor (NMDAR) encephalitis (NMDARE), characterized by antibodies against the NMDAR in the blood and spinal fluid of patients, is the most common form of autoimmune encephalitis (AE). A translational rodent model of NMDARE would allow for in-depth studies into AE pathophysiology, leading to advances in the diagnosis and treatment of this debilitating neuropsychiatric disorder. Design/Methods: 7-week-old female C57BL/6J mice were injected subcutaneously with an emulsion of complete Freund's adjuvant, attenuated Mycobacterium tuberculosis (TB), and a 30 amino acid peptide flanking the NMDAR NR1 subunit N368/G369 residue targeted by antibodies in NMDARE patients. Three different induction methods were tested by varying the amount and injection method of pertussis toxin, subcutaneous injection sites, reimmunization, and amounts of TB. Mice were bled biweekly and sacrificed at 2, 4, 6, 8, and 14 weeks. Serum and CSF NMDAR antibody titer; mouse behavior; hippocampal NMDAR protein and cluster density; and brain immune cell entry and cytokine content were examined. Results: Immunized mice had serum and CSF NMDAR antibodies. Mice exhibited behavioral changes, altered hippocampal NMDAR protein, brain immune cell entry, and elevated cytokines in their brains. Titers were higher and changes were sustained in reimmunized mice. Conclusions: Active immunization against the portion of the NMDAR targeted in patients with NMDARE resulted in robust production of NMDAR antibodies in the blood and spinal fluid, changes in hippocampal NMDAR protein, elevations in brain immune cells and cytokines, and behavioral changes in mice. Reimmunization was needed to sustain the responses. Active immunization therefore holds potential as a translational model of NMDARE, allowing for the creation of a novel generation of diagnostics and therapeutics.